Antenatal Bartters syndrome - Coutinho,Rita (2015)
Bartters syndrome is a rare renal tubular disorder with an autosomal recessive pattern of inheritanceand an estimated prevalence of 1 per million people. There are two distinct clinical presentations: antenatal Bartters syndrome and classical Bartters syndrome. Antenatal Bartters syndrome is considered the more severe form having its inception in utero. The typical features include early onset of foetal polyuria causing maternal polyhydramnios and preterm delivery, intrauterine growth restriction, postnatal polyuria and dehydration, nephrocalcinosis and osteopenia. We herein report a case of a newborn with antenatal Bartters syndrome, early suspected due to the familial and antenatal history. A 31 weeks gestation baby was born from consanguineous parents. Pregnancy was complicated with polyhydramnios at 24 weeks of gestation. The newborn developed polyuria, dehydration, electrolyte imbalances and metabolic alkalosis. Additionally, secondary hyperaldosteronism and hyperreninaemia with normal blood pressure were found. His older brother, also born preterm, had nephrocalcinosis and hypercalciuria attributed to prematurity and its complications. A diagnosis of Bartters syndrome type 2 was made by molecular study, which helped to clarify the clinical picture of his older brother. Antenatal Bartters syndrome manifestations can be neglected and undercovered by the diagnosis of prematurity. Hence, obstetricians and paediatricians should be aware of this rare disorder. A complete and careful clinical history is of the utmost importance to reach a definitive diagnosis